2019
DOI: 10.18488/journal.11.2019.82.88.97
|View full text |Cite
|
Sign up to set email alerts
|

Customer Care Service Management is Moving Forward to Achieve Sustainable Customer Retention in Every Industry. Does it play a Role to Increase Brand Retention?

Abstract: This is the first study that covers up the existing researcher gap between the retention-choice of consumers and the actual service facilities available for consumers. By conducting this study, we have concluded that a sustainable competitive advantage could be achieved by enhancing promised and acknowledgeable service to consumers because a balanced service delivery system would increase the retention level of consumers to stick with the same brand in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The role of price in influencing consumers' attitudes, and in turn affecting customer behaviour, is normal in the restaurant business, despite differences in consumer experience under different circumstances. Price variations in the restaurant business tend to influence customer expectations, evaluation, and decision making (Bhattacharjee, Jahanshahi, Polas, Hossain, & Asheq, 2019; Budiyanti & Patiro, 2018; Namin, 2017; Raju, 2018). The third hypothesis suggests that price perception of Islamic restaurants influences customers' revisit intentions.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…The role of price in influencing consumers' attitudes, and in turn affecting customer behaviour, is normal in the restaurant business, despite differences in consumer experience under different circumstances. Price variations in the restaurant business tend to influence customer expectations, evaluation, and decision making (Bhattacharjee, Jahanshahi, Polas, Hossain, & Asheq, 2019; Budiyanti & Patiro, 2018; Namin, 2017; Raju, 2018). The third hypothesis suggests that price perception of Islamic restaurants influences customers' revisit intentions.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…The welfare of distributors, workers, should be the priority. The effectiveness of emergency response is highly dependent on the quality and quantity of data available at any given time, and quality communication and cooperation between partners are vital (Bhattacharjee et al, 2019;Polas et al, 2019). Information sharing and cooperation are seen as effective strategies for the prevention and control of infectious diseases.…”
Section: Fig 1 Missing Figure Captionmentioning
confidence: 99%
“…Empathy has been linked to higher levels of customer satisfaction (Stević et al, 2021;Wieseke, Geigenmüller, & Kraus, 2012). Other studies have found that customers are not satisfied with the quality of the services when personnel lack empathy (Bhattacharjee, Jahanshahi, Polas, Hossain, & Asheq, 2019;Loke et al, 2011). Therefore, compassionate behavior towards employees fosters a favorable perception of businesses, enhancing their financial health (Khan & Fasih, 2014).…”
Section: Empathymentioning
confidence: 99%